Factors Influencing Employees’ Subjective Wellbeing and Job Performance During the COVID-19 Global Pandemic: The Perspective of Social Cognitive Career Theory - Lee, Tzai-Chiao; Yao-Ping Peng, Michael; Wang, Lin; Hung, Hao-Kai (Frontiers in Psychology, 2021)
The novel coronavirus disease that emerged at the end of 2019 began threatening the health and lives of millions of people after a few weeks. However, social and economic problems derived from COVID-19 have changed the development of individuals and the whole country. This study examines the work conditions of Taiwanese versus mainland China employees, and evaluates the relationship between support mechanisms and subjective well-being from a social cognitive career theory perspective. In this study, a total of 623 Taiwanese questionnaires and 513 mainland China questionnaires were collected to compare the two sample groups in development of employees’ subjective well-being. The results show that Taiwanese sample have more significant paths compared to mainland China employees in terms of prior knowledge, perceived organizational support, self-efficacy, employee employability, subjective well-being and job performance. Finally, based on the conclusions this study proposes some suggestions specific to theoretical mode for future study.